Exploring the Relationship Between Opioid Use Disorder and Major Depressive Disorder: A Case Study from Kentucky of United States - Hasan, Md Rakibul (Journal of Current and Advance Medical Research, 2025)
This case study explores the intricate and interconnected problems of drug usage and mental health in Kentucky, a state that has been greatly affected by the opioid epidemic and the high rate of mental illness. The study draws attention to the many difficulties that people with multiple diagnoses encounter, including as stigma, difficulty obtaining integrated treatment, and the need for extensive support networks. Through a thorough case study of a 35-year-old male patient from Louisville, Kentucky, who has been struggling with severe depressive disorder and opioid use disorder, the paper emphasizes how crucial integrated therapy methods are. By combining medication-assisted treatment (MAT), cognitive-behavioral therapy (CBT), and community support, the patient's journey from numerous unsuccessful rehabilitation endeavors to significant progress is meticulously documented. In treating drug use and mental health difficulties, the case study demonstrates the efficacy of creative alternatives including peer support groups, telemedicine services, and community-based therapies. In order to improve outcomes for people with dual diagnoses throughout the United States, the paper ends with suggestions for expanding integrated care models and a discussion of the wider implications for public health policy. Journal of Current and Advance Medical Research, January 2024;11(1):50-55